PENGARUH PEMBERIAN TEH TELUR TERHADAP LAMA PERSALINAN KALA 1 DI BPM “A” - Nina Fitri; Syahrifa Nur Aini (Maternal Child Health Care, 2021)
Prolonged labor is one of the causes of maternal death. The percentage of this case is 20% of all cases of causes of maternal death and 60% of cases of prolonged labor are inadequate. The inadequacy occurs because many women undergo an active phase for more than 6 hours and the cervical opening acceleration is less than 1 hour / cm. The purpose of this study was to determine The Effect of Egg Tea on the First Stage of Labor at BPM "A" Agam Regency in 2021. It was quasi experimental study with posttest design with only none equivalent control. This study was conducted at BPM "A" Agam Regency on February-March 2021. The samples were 20 people (1 control groups and 1 treatment groups). The data were collected through interviews and direct observation. The measuring instrument used pathograph. Then, it was analyzed by univariate and bivariate analysis by using the T test. The results of the study found the average childbirth in the control group was 3.3 hours and the average delivery in the treatment group was 2.6 hours. There is an effect of egg tea administration on the duration of delivery when I, with the result of a symp.sig value of 0.026 < α 0.05. In short, there was an effect of egg tea on the duration of the first stage of labor at BPM "A" Agam Regency in 2021. It is hoped that midwives improve the quality of delivery to women who give birth by carrying out proper handling of women who are at risk of dehydration and lack of energy during the labor process. how to rehydrate by consuming egg tea. Keywords: First Stage Labor, Duration of First Stage Labor, Egg Tea